PHYSIOTHERAPY PROTOCOL FOR TOTAL KNEE ARTHROPLASTIES (Cuestiones de Fisioterapia, 1999)
A great number of patients suffering from arthrosis of the knee and other physical disorders such limitations, pain, etc., can see their problems alleviated. According to our research, modern surgery can substitute the former and ineffective treatment by an arthroplasty. Therefore, the purpose of this article is to show the techniques that we follow in the Hospital Cllnico Universitario de Valencia in relation to the treatment of arthroplasties of the knee the type of called Hermes. We considered this research and the result very successful